(untitled) (World Economics and Finance Bulletin, 2026)
This study examines methodological issues and practical challenges in auditing liabilities in joint-stock companies and proposes an improved audit framework aligned with International Standards on Auditing (ISA) and International Financial Reporting Standards (IFRS). Liabilities represent a critical component of financial statements and directly influence solvency, leverage, and financial sustainability indicators. However, auditing liabilities involves heightened risk due to complex valuation methods, discounting procedures, effective interest rate calculations, and fair value assessments. The research identifies key audit risk areas and develops an enhanced risk-based audit approach, including refined substantive procedures and strengthened audit evidence collection mechanisms. The proposed model contributes to improving audit quality, reducing detection risk, and enhancing the reliability of financial reporting in joint-stock companies.